2010
DOI: 10.1007/s11739-010-0382-9
|View full text |Cite
|
Sign up to set email alerts
|

A study on QT interval in patients affected with inflammatory bowel disease without cardiac involvement

Abstract: Cardiac involvement has been studied quite extensively in patients affected by inflammatory bowel disease but, as of now, there is no data regarding QT alterations which are well known to be linked to the risk of dangerous arrhythmias. In this study, QT parameters were digitally measured on standard 12-lead ECG in a population of 20 patients affected by inflammatory bowel disease (IBD), with no prior (recent or old) history of cardiac disease and no evidence of electrolyte imbalance. Eighteen healthy subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…This reduction in Ca2+ levels may be responsible for depressed cell contractility and the development of aberrant sparks or hump-like depolarizations, which are risk factors for the occurrence of an arrhythmic event. Patients with ankylosing spondylitis or inflammatory bowel diseases often have a prolonged QT interval (14), which, according to some authors, can be restored by treatment with infliximab (15). Neither of our patients had alterations of the QT interval, as emerged by an electrocardiographic test performed at baseline and after 12 month of treatment wit CZP.…”
Section: Case #2supporting
confidence: 45%
“…This reduction in Ca2+ levels may be responsible for depressed cell contractility and the development of aberrant sparks or hump-like depolarizations, which are risk factors for the occurrence of an arrhythmic event. Patients with ankylosing spondylitis or inflammatory bowel diseases often have a prolonged QT interval (14), which, according to some authors, can be restored by treatment with infliximab (15). Neither of our patients had alterations of the QT interval, as emerged by an electrocardiographic test performed at baseline and after 12 month of treatment wit CZP.…”
Section: Case #2supporting
confidence: 45%
“…Similar autonomic imbalance may have a bearing on ventricular repolarisation abnormalities and further the pathogenesis of P-wave and QT interval prolongation in IBD patients. In the other study by Curione et al [28], QTc interval and QTcdisp values were both considerably prolonged in IBD patients compared with individuals in the control group. The literatures suggested that sympathetic activity changes could be the reason for QT and QTc interval alterations and increased QT dispersion and QTc dispersion of ventricular repolarisation [29, 30].…”
Section: Discussionmentioning
confidence: 72%
“…The authors argued that the QTc and QTc dispersion measurements of the patients with IBD were longer than those of the healthy controls and concluded that it might be due to the systemic inflammation. 18 We have known that AS is one of the well-known systemic inflammatory diseases, which can also affect the cardiovascular system just as IBD. Consequently, if we suppress or control the inflammation, QT intervals may be shortened.…”
Section: Discussionmentioning
confidence: 99%